Assessment of avalanche runout distance at Krasnaya Polyana in the absence of direct observational data - E. D. Zhukova; A. S. Turchaninova; N. V. Kovalenko; D. A. Petrakov (Лëд и снег)
The purpose of this work was the effort to estimate the distance of snow avalanche runout on the undeveloped slope of the Aibga ridge in Krasnaya Polyana using the landscape-indicative method together with statistical analysis and numerical simulation.   The approach to solving this problem is considered, combining: analysis of snow depth data and information about avalanches in the adjacent territory, identification of phyto-indicative evidences of the avalanche activity obtained during field observations and analysis of remote sensing data. The article describes in details each of the methods used, as well as contributions of them to the general methodology for estimating the runout range and the boundaries of areas of the avalanche distribution. The analysis of Earth remote sensing data, taking account of results of field surveys of key sites, was based on the landscape-indication method, which allowed us to determine the boundaries of areas of the impact of avalanches with different occurrences basing on observations of the vegetation changes. In addition, the distances of the avalanche runouts were calculated using graph-analytic method (SP 428.1325800.2018) and the RAMMS model. The results of the study show that several methods used in this work complement each other and provide more reasonable and accurate estimation of the avalanche range and the lateral boundaries of distribution of them. That is important for a territorial planning, making design decisions and choosing measures to ensure the safety of people and infrastructure objects if any recreational development of the territory is to be considered.